The Concept of Teachers and Its Scope - Muchamad Toif Chasani (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
This paper aims to explain the position of the teacher as the subject of education, which is seen from the ethics of the teacher, the basic skills that must be possessed by the teacher, the duties and roles of the teacher, and the pattern of recruitment to become a teacher. Teachers as central figures in education must have sufficient competence and qualifications from their background, ethics, work or activities other than being a teacher. This research method uses literature review, with primary and secondary data sources, and the analysis used is content analysis. The results of this study indicate that the teacher is a central figure in education. His position cannot be replaced and at the same time serves as an example for students in particular and society in general. As an example, teachers cannot avoid the professional ethics attached to them. Apart from that, the pattern of teacher recruitment must also be carried out not only looking at the cognitive aspect alone, but other aspects such as adab and morality must be the main consideration.